THE RELATIONSHIP OF EMPLOYEE COMMUNICATION AND ADDITIONAL INCOME (TPP) WITH EMPLOYEE PERFORMANCE AT THE COMMUNICATION AND INFORMATICS DEPARTMENT (KOMINFO) KAUR REGENCY - Dena Leftiani; Karona Cahya Susena; Sri Handayani (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2020)
The purpose of this study was to determine the relationship between communication and additional income of employees with performance in the Kaur district communication and informatics department. This type of research uses quantitative descriptive. The sampling technique used census techniques as many as 29 respondents taken from the civil servants of the communication and informatics department of the district of Kaur. Analysis of research is using Pearson correlation and hypothesis test using the t-test. From the discussion about the relationship between communication and additional employee income (TPP) with the performance of civil servants in the KOMINFO Office of Kaur Regency that has been described, then conclusions can be drawn, There is a significant relationship between communication and employee performance. This is evidenced by the calculated r value of 0.411 with moderate interpretation criteria. While the value of tcount of 2,342 is greater than the ttable of 2,052 which results in H0 being rejected and Ha accepted, which means the research hypothesis is accepted. There is no significant relationship between additional employee income and performance. This is evidenced by the calculated r value of -0.061 with very weak interpretation criteria. While the value of tcount of -0.316 is smaller than ttable of 2.052 which results in H0 being accepted and Ha being rejected, which means the research hypothesis is rejected.